Evaluating the role of the social worker working in correctional institution: Afield study on the social Education House for Boys and Girls in Sharjah - alotaibi, kafaf abdullah; Al-Othman, Hussein Muhammad (Al-Adab Journal, 2020)
This study aims to identify and evaluate the role of social workers who work at the Home of Social Education, and to understand the obstcals that face the social workers in order to recommend suggestions regarding the programs and activities the home, of which are intended to change the delinquent behavior of the adolescents inmates, hence, enabling them to go back to their community and function normally. A special questionnaire was designed and applied to (22) adolescents' inmates and (5) social workers at the Home of Social Education.Results support the hypothesis of the study, and that is: social workers positively deal with the inmates, they are knowledgeable of the psychological and behavioral characteristics of individuals, are characterized by integrity and being neutral. They also greatly contribute in modifying the behavior of the inmates by effectively applying religious, cultural and recreational activities.The results of the study concerning the main obstacles that are faced by the social worker in performing their job was incomplete inmates' records, lack in number of social workers, and lack available resources.